Renmin gongchen - Li Linxiang,
'Heroes of the People'. Printno. 8027.8750. See also BG E13/17-27. Place of persons f.l.t.r.: Luo Ronghuan, He Long, Ye Jianying, Peng Dehuai, Liu Bocheng, Zhu De, Xu Xiangqiang, Nie Rongzhen, Chen Yi.